APA MAKNA âKEUNTUNGANâ BAGI PROFESI DOKTER? - Sari, Dian Purnama (Jurnal Akuntansi Multiparadigma, 2014)
Abstract: What is the meaning of âprofitâ for doctor profession? This researchâs goal is to understand the meaning of âprofitâ which is seen from doctorâs side. With Intensionalism Hermeneutic as research method, this research concludes that there are four meanings of âprofitâ for doctor profession. The first meaning is material âprofitâ which is called as saving to fulfill doctorâs needs. The second meaning is spiritual âprofitâ addressed for fellow being and return to God. The third meaning is prestige âprofitâ which is respected enough in society. And the fourth meaning is satisfaction of mind âprofitâ when the patient is cured and healthy.Abstrak: Apa makna âkeuntunganâ bagi profesi dokter? Tujuan penelitian ini adalah untuk memahami makna âkeuntunganâ yang dilihat dari sudut pandang profesi dokter. Dengan menggunakan hermeneutika intensionalisme sebagai metode penelitian, penelitian ini menyimpulkan empat makna âkeuntunganâ bagi profesi dokter. Makna pertama adalah âkeuntunganâ materi yang disebut tabungan untuk memenuhi kebutuhan dokter. Makna kedua adalah âkeuntunganâ spiritual dalam selalu menolong orang lain maupun mengembalikannya kepada Tuhan. Makna ketiga adalah âkeuntunganâ martabat yang disegani oleh masyarakat. Makna keempat adalah âkeuntunganâ kepuasan batin apabila pasien yang dirawatnya dapat sembuh.